2014
DOI: 10.3390/molecules191117314
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Flavonoid Compounds in the Flavedo and Juice of Two Pummelo Cultivars (Citrus grandis L. Osbeck) from Different Cultivation Regions in China

Abstract: Abstract:The objective of this study was to investigate the effect of different cultivation regions on the pattern and content of flavonoids in two pummelo cultivars (C. grandis L. Osbeck) in China. Results showed that similar patterns of flavonoids were observed in the flavedo or juice of each pummelo cultivar from these cultivation regions, whereas the individual flavonoid content showed unique characteristics. Naringin, the predominant flavanone glycoside, showed the highest content in both flavedo and juic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 23 publications
5
12
0
Order By: Relevance
“…The compounds detected are reported in Table and are compared with those presented in the literature. And several of the flavonoids identified in toranja are consistent with others varieties of citrus (Zhang et al, ).…”
Section: Resultssupporting
confidence: 82%
“…The compounds detected are reported in Table and are compared with those presented in the literature. And several of the flavonoids identified in toranja are consistent with others varieties of citrus (Zhang et al, ).…”
Section: Resultssupporting
confidence: 82%
“…Paeonia seed oils related to geographical distribution has been implemented, and the results showed that two clusters had significant differences in longitude and altitude . It has also been accepted that the accumulation of secondary metabolites in fruits was affected by cultivation region with different climates and environmental features . Similar results were obtained in the research of volatile profile from pummelo cultivars .…”
Section: Resultsmentioning
confidence: 53%
“…It has been confirmed that fruit genotype essentially determines the secondary metabolite patterns in fruits, whereas cultivation conditions also play an important role in regulating the accumulation level of secondary metabolites [ 12 , 13 , 14 , 15 ]. Our previous study has confirmed that the phenolic compound profile in flavedo and juice of the same pummelo cultivar exhibited regional differences [ 16 ]. In the present study, we further attempted to investigate if the genotype and cultivation conditions could also alter the composition of volatile compounds in pummelo.…”
Section: Introductionmentioning
confidence: 64%
“…Secondary metabolites, including volatile compounds, are generally biosynthesized from primary nutrients in plant as a response to fruit development and environmental changes [ 5 , 14 ]. Secondary metabolites can play important roles in affecting the sensory attributes and nutritional quality of fruits and provide fruits with multiple bioactive properties [ 14 , 16 ]. Regarding their chemical nature, volatile compounds can be divided into aldehydes, alcohols, ketones, esters, terpenes and other volatiles.…”
Section: Resultsmentioning
confidence: 99%